Dynamic Response of Two-Electrode Distributed Feedback Laser for Stable Signal Mode Operation - Hamza Bousseta; A. Zatni; A. Amghar; A. Moumen; A. Elyamani (Institute of Advanced Engineering and Science, 2015)
The longitudinal spatial hole burning (LSHB) effect has been known to limit the performance of distributed feedback (DFB) semiconductor lasers to achieve a better dynamic signal mode operation (DSMO). So, in order to ensure a stable (DSMO), we propose a novel device design of two electrode DFB lasers with longitudinal variation in the coupling coefficient (distributed coupling coefficient (DCC)), the structure also contains a phase shifted in middle of the cavity. By means of the finite difference time domain (FDTD) numerical method, we analyze dynamic response of our structure and we also compare the results with the conventional two electrode DFB laser (TE-DFB). The numerical simulation shows that, a better dynamic signal mode has been achieved by TE-DCC-DFB lasers in comparison with TE-DFB laser due to its better and high side mode suppression ratio (SMSR). Therefore, the TE-DCC-DFB lasers will be useful to extend the transmission distance in optical fiber communication systems.